(untitled) (Heritage, 2023)
Interaction and communication are essential features of education, so in interactive (communicative) pedagogy, education is defined as a kind of interaction between educators and learners - teachers and students. In an interactive educational environment that implies respect for the principles of pedagogical communication, the educational influences are more emphasized and focused on personality development, and the connections between the subjects of the educational process are firm and strong. In this sense, the paper discusses the implications of teaching as an interactive process on learning outcomes and the position of students in it. In the conclusion, it is emphasized that active interaction between teachers and students conditions greater student autonomy, which increases the possibilities for the development of a flexible, resilient, creative, and above all, responsible and free individual. The prerequisites for creating more optimal conditions for learning and the application of more purposeful interactions that would serve the purpose of successful teaching and learning and personality development were also highlighted.